2002
DOI: 10.1046/j.1365-2230.2002.01004.x
|View full text |Cite
|
Sign up to set email alerts
|

Associations between human leukocyte antigens and leprosy in the Turkish population

Abstract: Leprosy is a chronic infection caused by an intracellular microorganism. Genetic predisposition to both disease susceptibility and to host immunological response has been postulated for many years. The aim of this study was to determine whether there is HLA-linked susceptibility to leprosy and its different types. HLA-class I (A, B, C) and II (DR, DQ) antigen frequencies in 80 patients with leprosy (35 borderline lepromatous, 25 lepromatous, 15 borderline tuberculoid, five tuberculoid) were compared with those… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2003
2003
2011
2011

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 14 publications
(51 reference statements)
0
19
0
Order By: Relevance
“…Increased frequencies of HLA A2, A11, B40, and DR2 were observed among the leprosy patients from South India [23]. Recently, HLA A9, A10, A32, B5, B21, Bw4, Bw6, Cw1, and Cw2 were found to be significantly more frequent among Turkish leprosy patients [24]. In all these earlier studies, the HLA were determined by conventional techniques that might have resulted in a lower resolution of HLA types.…”
Section: Resultsmentioning
confidence: 99%
“…Increased frequencies of HLA A2, A11, B40, and DR2 were observed among the leprosy patients from South India [23]. Recently, HLA A9, A10, A32, B5, B21, Bw4, Bw6, Cw1, and Cw2 were found to be significantly more frequent among Turkish leprosy patients [24]. In all these earlier studies, the HLA were determined by conventional techniques that might have resulted in a lower resolution of HLA types.…”
Section: Resultsmentioning
confidence: 99%
“…Few studies reported association of leprosy with HLA-A and B [8,9,25,26]. Interestingly, one of these studies showed significantly decreased of B‫64ء‬ in multibacillary patients from southern Chinese (OR ϭ 0.28, p Ͻ 0.01) but not in paucibacillary patients [26].…”
Section: Discussionmentioning
confidence: 99%
“…HLA-class I antigens A9, A10, A32, B5, B21, Bw4, Bw6, Cw1, Cw2, and HLA-class II antigens DR9, DR10, DRw52, DQ1, DQ3 were associated with leprosy. HLA-class I antigens A3, B44, B49, and HLA-class II antigen DQ5 were found protective in a Turkish population [51]. HLA-B46 allele and HLAB46/MICA-A5 haplotype protects against MB leprosy in Chinese population [52].…”
Section: Genes and Its Variants Associated With Leprosy Types And mentioning
confidence: 99%